Argon plasma coagulation of actinic keratoses imaged by optical coherence tomography: An in vivo study indicating a possible lesion‐directed treatment. Issue 10 (9th July 2018) - Schmitz, Lutz; Hessam, Schapoor; Scholl, Lisa; Reitenbach, Sarah; Segert, Marc H.; Gambichler, Thilo; Stockfleth, Eggert; Bechara, Falk G.
Abstract : Actinic keratoses (AKs) can progress into invasive squamous cell carcinoma and thus may become a life threatening disease. Argon plasma coagulation (APC) might complement the therapeutic armamentarium in particular for AK lesions. However, there is no data on APC‐induced micromorphological changes following the treatment of AKs. We aimed to determine in vivo APC‐induced effects on the epidermis and dermoepidermal junction (DEJ) zone in AK lesions. We performed APC in 108 AKs using the spray mode with a power setting of 15 W and a flow rate of 2.0 L/min. Before and after the intervention, optical coherence tomography (OCT) was performed. After APC, 74.2% (46/62) lesions presented with clearly demarcated DEJ and without any epidermal tissue left, 25.8% (16/62) of treated lesions showed residual epidermal tissue left. In 19.4% (12/62), parts of the DEJ and in 6.5% (4/62), the entire DEJ could not be discriminated. The χ 2 test showed a significant ( P = 0.0025) association between the presence of hyperkeratosis prior to APC and intact DEJ after APC. In conclusion, APC as shown by OCT is a well controllable treatment modality for AKs causing only limited damage to dermal tissue. Further studies are needed to evaluate clinical outcome as well as recurrence rates. Abstract : Argon plasma coagulation (APC) might complement ablative treatment modalities of epithelial neoplasms as indicated by recently reported ex vivo data. Based on these results, actinic keratoses (AKs) were treated by APC and the micromorphological changes were investigated in vivo by means of optical coherence tomography. APC showed to be a well controllable technique causing limited damage to dermal tissue.